1983
DOI: 10.1266/jjg.58.153
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism and evolution in parthenogenetic animals. XII. Observations on Japanese polyploid curculionidae (coleoptera).

Abstract: Triploid and pentaploid individuals of Scepticus insularis, originating from Honshu and Hokkaido, as well as tetraploid individuals of Callirhopalus bifasciatus and Catapionus gracilicornis have been assayed by starch gel electrophoresis.All weevils were parthenogenetic females.The results indicate that there is variation within a parthenogenetic population and that different degrees of polyploidy appear identical. This indicates that the degrees of polyploidy in parthenogenetic weevils originate at abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
(4 reference statements)
1
5
0
Order By: Relevance
“…The results confirm a similar observation made earlier for triploid and pentaploid Scepticus insularis (Takenouchi et al 1983) and Polydrosus mollis (Lokki et al 1976), where an identical overall genotype (phenotype) was found in diploid and triploid parthenogenetic samples. The multiple spindle hypothesis of Suomalainen (1940Suomalainen ( , 1947 is in agreement with these observations.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results confirm a similar observation made earlier for triploid and pentaploid Scepticus insularis (Takenouchi et al 1983) and Polydrosus mollis (Lokki et al 1976), where an identical overall genotype (phenotype) was found in diploid and triploid parthenogenetic samples. The multiple spindle hypothesis of Suomalainen (1940Suomalainen ( , 1947 is in agreement with these observations.…”
Section: Discussionsupporting
confidence: 92%
“…May 1983. The enzyme assay methods and controls are as described by Takenouchi et al (1983). The same sixteen enzyme systems, coding for 21 loci, were assayed (cf.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, one would expect a greater fraction of diploid forms in the parthenogenetic species, if secondary contacts were occuring more regularly. Secondly, a great majority of attempts to achieve matings between a parthenogenetic female and a male of a bisexual population of the nominal species have failed ( Mockford 1971; Smith and Virkki 1978; Takenouchi et al 1983). Parthenogenetic and bisexual forms behave like separate species, i.e.…”
Section: Discussionmentioning
confidence: 99%